2021
DOI: 10.1101/2021.01.10.21249538
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vulnerabilities in child wellbeing among primary school children: a cross-sectional study in Bradford, UK

Abstract: ObjectiveTo describe the prevalence of factors related to wellbeing among primary school children in a deprived multi-ethnic community.Design and participantsCross-sectional survey of 15,641 children aged 7-10 years in Born in Bradford’s Primary School Years study: whole-classroom samples in 89 Bradford primary schools between 2016 and 2019.Main outcome measuresPrevalence estimates by ethnicity (%, 95% CI) of single and multiple vulnerabilities in child wellbeing within and across four domains (home, family, r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Experiencing social stigma can lead to psychological stress in the individual, and evidence for a link between both positive and negative social relationships and mental health status has been published (16). Substantial evidence shows that caregivers of children with developmental disabilities are more susceptible to developing anxiety, depression, and a range of physical symptoms and illnesses (33). High levels of stress were found to be a likely mediator in this Syndemic model (34).…”
Section: Syndemic Contributors To Mental and Physical Illness In Lite...mentioning
confidence: 92%
“…Experiencing social stigma can lead to psychological stress in the individual, and evidence for a link between both positive and negative social relationships and mental health status has been published (16). Substantial evidence shows that caregivers of children with developmental disabilities are more susceptible to developing anxiety, depression, and a range of physical symptoms and illnesses (33). High levels of stress were found to be a likely mediator in this Syndemic model (34).…”
Section: Syndemic Contributors To Mental and Physical Illness In Lite...mentioning
confidence: 92%
“…Two recent studies had collected data on the BiB children and their families prior to the pandemic: BiB Growing Up (BiBGU), which collected data from BiB cohort families in community-based assessments between 2017–2020, and BiB Primary School Years (PSY), which collected data from children aged 6–11 in school-based assessments between 2016–2019 (see Bird et al , 2019 ). At the time that the BiB COVID-19 study took place, 5,300 children had participated in BiBGU and, 15,641 children from 89 primary schools participated in PSY, of whom 6,147 were BiB children ( Pickett et al , 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Ethical approval was obtained from the National Health Service Health Research Authority Yorkshire and the Humber (Bradford Leeds) Research Ethics Committee (reference: 16/YH/0062). Children self-completed a survey (“Me and My Life”), developed using questions derived from the Millennium Cohort Study, the International Survey of Children’s Wellbeing and the Avon Longitudinal Study of Parents and Children ( Pickett et al , 2021 ). Amongst these questions, children provided information on self-reported wellbeing by being asked how often they felt happy and sad with potential response categories: always, sometimes, never.…”
Section: Methodsmentioning
confidence: 99%
“…This critical period involves rapid biological, psychological and social development, and is a high risk period for the onset of mental ill-health ( Blakemore, 2019 ; Paus et al , 2008 ). Indeed, data collected on BiB children during primary school found that more than half of the 16,000 children who took part reported being bullied some or all of the time, a third said they kept their worries to themselves and a quarter worried all the time about how much money their families have ( Pickett et al , 2021 ). All three are key experiences of socioeconomic contexts that are highly relevant to mental health across the life-course.…”
Section: Introductionmentioning
confidence: 99%